Vrodená bránicná hernia prejavujúca sa po novorodeneckom období - Drahovský, P; Dankovcík, J; Bodnárová, A; Drahovská, I; Sabovcík, R (Rozhledy v chirurgii, 1999)
In the course of 16 years at the authors department 46 children with congenital malformation of the diaphragm were operated. This group comprised 12 children (26%) where the first symptoms developed only after the neonatal period. Most frequently the symptoms were repeated respiratory infections (in 9 children), and gastrointestinal complaints in 4 children. The children were operated electively: in 8 patients a left-sided Bochdalek hernia (1x with a sac) was involved, 3 children had a hiatus hernia and one child a Morgagni hernia. After surgery no early or late complications were recorded. In the discussion the authors deal with inborn diaphragmatic hernia with a late manifestation which is mainly a diagnostic problem. Therefore, based on their own experience and consistent with data in the literature, the authors recommend careful aimed examination of children with chronic non-specific respiratory or gastrointestinal complaints.
Keywords: Hernia, Diaphragmatic; novorozenec; Infant, Newborn; předškolní dítě; Infant; Humans; lidé; vrozená brániční kýla; kojenec; Child, Preschool; Hernias, Diaphragmatic, Congenital; brániční hernie